Module-scale simulation of forward osmosis module-part A: Plate-and-frame - Bilad, M.R. (Universitas Pendidikan Indonesia, 2016)
In forward osmosis (FO), a semi-permeable membrane separates a concentrated draw and a diluted feed solution. FO has emerges as a promising alternative for various applications. To support further development of FO process, a larger scale optimization is required to accurately envisage the most critical factors to be explored. In this study, we applied a mass-transfer model coupled with the mass conservation and area discretization to simulate the performance of plate-and-frame FO modules (10 sheets of 1x1m). Effects of numerous parameters were simulated: modes, flow orientations (co-, counter-and cross-currents), spacers and spacer properties, membrane parameters and operational parameters. Results show that counter-current flow orientation offers the highest flux with minimum spatial distribution. Module performance can be improved by developing FO membrane through reducing membrane structural (S) parameter and increasing water permeability (A): increasing A-value only significant at low S-value, and vice versa (i.e., for A-value of 1 LMH/atm, S-value must be below 50 Âµm). Furthermore, inclusion of spacer in the flow channel slightly increases the flux (merely up to 2). Module performance can also be enhanced by increasing feed flow rate, lowering solute in the feed and increasing solute in the draw solution. Â© 2016 Tim Pengembang Journal UPI.